Wireless Wakeups Revisited: Energy Management for VoIP Over Wi-Fi Smartphones - Agarwal, Yuvraj; Chandra, Ranveer; Wolman, Alec; Bahl, Paramvir; Chin, Kevin; Gupta, Rajesh (ACM/USENIX Mobile Systems, Applications, and Services (MobiSys), 2007)
IP based telephony is rapidly gaining acceptance over traditional means of voice communication. Wireless LANs are also becoming ubiquitous due to their inherent ease of deployment and decreasing costs. In enterprise Wi-Fi environments, VoIP is a compelling application for devices such as smartphones with multiple wireless interfaces. However, the high energy consumption of Wi-Fi interfaces, especially when a device is idle, presents a significant barrier to the widespread adoption of VoIP over Wi-Fi. To address this issue, we present Cell2Notify, a practical and deployable energy management architecture that leverages the cellular radio on a smartphone to implement wakeup for the high-energy consumptionWi-Fi radio. We present detailed measurements of energy consumption on smartphone devices, and we show that Cell2Notify can extend the battery lifetime of VoIP over Wi-Fi enabled smartphones by a factor of 1.7 to 6.4.